Perturbações antrópicas em espécies alvo da ictiofauna da bacia do Rio Teles Pires - Matos, Liliane Stedile de (2018)
The environmental integrity of the Teles Pires River basin and its fishing resources is threatened due to the region's economic activities, such as mining, cattle raising, agriculture, predatory fishing and, recently, the implementation of hydroelectric plants. The present thesis, aimed at analyzing anthropic disturbances in the target species of the ichthyofauna of the Teles Pires River, is composed of four chapters. In the first chapter, it is verified whether the supply of fresh soybean in barley would be influencing the weight-length relationship and the condition factor of the Brycon falcatus fish. It is concluded that, to date, the supply of fresh soybeans in grains did not interfere with the well-being of B. falcatus collected in this river basin. In the second chapter, interviews are aimed at investigating artisanal professional fishermen if there was a decline in the catch of matrinxã fish and what are the main causes of this. It is concluded that the interviews with fishermen working on the Teles Pires river in the municipality of Sinop allowed us to observe their perceptions regarding the problem of the fall in the fish stock of the matrinxã fish. In the third chapter, the concentration of total mercury (THg) in the muscle, gills and liver of B. falcatus is investigated for bioaccumulation and restrictions for consumption. It is concluded that the concentrations of THg in the B. falcatus muscle are below the limit recommended by the World Health Organization for people consuming up to 250 g of fish per week, risk of deleterious effects on human health may exist if there is a greater consumption of B. falcatus. In the fourth chapter, levels and bioaccumulation of THg in the muscle, liver, kidneys and gills of detritus and carnivorous fish (Hydrolycus armatus, Hydrolycus tatauaia, Cichla mirianae and Prochilodus nigricans) in rivers of the Teles Pires basin are evaluated. It was concluded that the concentrations of THg did not interfere in the well being and sanity of the evaluated organisms, since the values of the condition factor and the hepatosomatic index were not related to the THg of the muscle.